Influence on interradicular bone volume of Invisalign treatment for adult crowding with interproximal enamel reduction: a retrospective three-dimensional cone-beam computed tomography study - Andreas Hellak; Nicola Schmidt; Michael Schauseil; Steffen Stein; Thomas Drechsler; Heike Maria Korbmacher-Steiner (BMC, 2018)
Abstract Background The aim of this study was to use three-dimensional datasets to identify associations between treatment for adult crowding, using Invisalign aligner and interproximal enamel reduction (IER), and changes in the volume of interradicular bone. Methods A total of 60 cone-beam computed tomography (CBCT) scans from 30 adult patients (28 women, two men; 30 CBCTs pre-treatment, 30 post-treatment) were examined retrospectively in order to measure bone volume three-dimensionally. The patients' average age was 36.03 ± 9.7 years. The interradicular bone volume was measured with OsiriX at four levels in the anterior tooth areas of the maxilla and mandible. Differences in bone between T0 and T1 were analyzed with IBM SPSS 21.0 using the Wilcoxon test for paired samples. Results Overall, a slight increase in the quantity of bone was found (0.12 ± 0.73 mm). There was a highly significant increase in bone in the mandible (0.40 ± 0.62 mm; P <  0.001), while in the maxilla there was a slight loss of bone, which was highly significant in the apical third (− 0.16 ± 0.77 mm; P = 0.001). Conclusions Overall, treatment for adult crowding using an aligner and IER appears to have a positive effect on interradicular bone volume, particularly in patients with severe grades of the condition (periodontally high-risk dentition). This effect is apparently independent of IER. This is extremely important with regard to the treatment outcome, since IER and root proximity have been matters of debate in the literature and teeth should remain firmly embedded in their alveolar sockets.